Origin of Dolomites in the Baluti Formation (Late Triassic), Galley Derash Area, N-Iraq: Petrography, Textural and Diagenetic Properties - Al-Mashaikie, Sa’ad Zeki A. Kader; A. Razzak, Suhad Khalaf (Iraqi Journal of Science, 2022)
Baluti Formation of the Rhaetian (Late Triassic) age is composed mainly of dolomite, the unit formed with dolomitic limestone, dolomitic breccias and limestone begins with gray or dark gray colored and sugar textured dolomitic limestones including micrite with shale horizons. Baluti Formation was deposited in carbonate platform, and slumped to deeper margins forming carbonate debrites and breccias of various types.Petrographic examination of the dolomites reveals various crystal habits and textures of the dolomites. Planktonic bivalve, calcisphere and echinoid spicules were found in the Baluti Formation settled in deep-margin carbonate environment. Nine dolomite-rock textures were identified and classified according to the crystal-size distribution and crystal-boundary shape. These are made of unimodal, 1) very fine to fine-crystalline planar-s (subhedral) mosaic dolomite; 2) unimodal, medium to coarse-crystalline planar-s (subhedral) mosaic dolomite; 3) coarse to very coarse crystalline planar-s (subhedral) dolomite; 4) medium to coarse-crystalline planar-e (euhedral) mosaic dolomite; 5) medium to coarse-crystalline planar-e (euhedral) dolomite; 6) coarse to very coarse-crystalline non-planar-a (anhedral) dolomite; 7) coarse to very coarse-crystalline non-planar-c (cement) dolomite; 8) polymodal, planar-s (subhedral) to planar-e (euhedral) mosaic dolomite. Dolomitization is closely associated with the development of secondary porosity; dolomitization pre and post diagenetic dissolution and corrosion and no secondary porosity generation is present in the associated limestones. The most common porosity types are non-fabric selective moldic and vugy porosity and intercrystalline porosity. These porous zones are characterized by late-diagenetic coarse-crystalline dolomite, whereas the non-porous intervals are composed of dense mosaics of early-diagenetic dolomites. The distribution of dolomite rock textures indicates that porous zones were preserved as limestone until late in the diagenetic history, and were then subjected to late-stage dolomitization in a medium burial environment, resulting in coarse-crystalline porous dolomites. Baluti dolomites have been formed as early diagenetic at the tidal-subtidal environment and as a late diagenetic at the shallow-deep burial depths.